High-efficiency and stable quasi-solid-state dye-sensitized solar cell based on low molecular mass organogelator electrolyte. Issue 5 (17th December 2014) - Tao, Li; Huo, Zhipeng; Ding, Yong; Li, Yi; Dai, Songyuan; Wang, Lu; Zhu, Jun; Pan, Xu; Zhang, Bing; Yao, Jianxi; Nazeeruddin, Mohammad K.; Grätzel, Michael
Abstract : A quasi-solid-state dye-sensitized solar cell with high photoelectric conversion efficiency (9.61%) and long-term stability is fabricated with a low molecular mass organogelator based gel electrolyte. Abstract : The highest photoelectric conversion efficiency (9.61%) for a quasi-solid-state DSSC (QS-DSSC) based on a low molecular mass organogelator (LMOG) is achieved using N, N ′-1, 5-pentanediylbis-dodecanamide as a LMOG in conjunction with a TiO2 photoanode of sub-microspheres sensitized with a high-absorptivity Ru complex (C101). The competition of interfacial kinetic processes between the recombination of the dye cations with photoinjected electrons and the regeneration of the dye cations by I − is investigated by transient adsorption measurements. The data revealed that there is an efficient interfacial charge separation at the TiO2 photoelectrode/electrolyte interface and the dye is rapidly regenerated, which contributes to the high photocurrent. Furthermore, using electrochemical impedance spectroscopy (EIS) and controlled intensity modulated photocurrent/photovoltage spectroscopy (IMPS/IMVS), it is determined that the negative shift of TiO2 conduction band edge of the QS-DSSC contributes to the high V oc . Moreover, the QS-DSSC exhibits significantly improved stability during the accelerated thermal and light-soaking test. During the accelerated aging test, there is almost no change in the short-circuit current density ( J sc ) in the QS-DSSC, while the J sc of the liquid electrolyte based DSSC decreases sharply. These results are very important for the application and commercialization of DSSCs.